The Evolving Role of Nonsteroidal Anti-Inflammatory Drugs in Colon Cancer Prevention: A Cause for Optimism - Rigas, Basil (J Pharmacol Exp Ther, 2015)
Colorectal cancer (CRC) is a serious yet preventable disease. The low acceptance and cost of colonoscopy as a screening method for CRC make chemoprevention an important option. Nonsteroidal anti-inflammatory drugs (NSAIDs), not currently recommended for CRC prevention, have the potential to evolve into the agents of choice for this indication. Here, we discuss the promise and challenge of NSAIDs for this chemopreventive application. Multiple epidemiologic studies, randomized clinical trials (RCTs) of sporadic colorectal polyp recurrence, RCTs in patients with hereditary colorectal cancer syndromes, and pooled analyses of cardiovascular-prevention RCTs linked to cancer outcomes have firmly established the ability of conventional NSAIDs to prevent CRC. NSAIDs, however, are seriously limited by their toxicity, which can become cumulative with their long-term administration for chemoprevention, whereas drug interactions in vulnerable elderly patients compound their safety. Newer, chemically modified NSAIDs offer the hope of enhanced efficacy and safety. Recent work also indicates that targeting earlier stages of colorectal carcinogenesis, such as the lower complexity aberrant crypt foci, is a promising approach that may only require relatively short use of chemopreventive agents. Drug combination approaches exemplified by sulindac plus difluoromethylornithine appear very efficacious. Identification of those at risk or most likely to benefit from a given intervention using predictive biomarkers may usher in personalized chemoprevention. Agents that offer simultaneous chemoprevention of diseases in addition to CRC, e.g., cardiovascular and/or neurodegenerative diseases, may have a much greater potential for a broad clinical application.